Find the roots of the following quadratic equations by factorisation 2*x*^{2} + *x* – 6 = 0

Advertisement Remove all ads

#### Solution

2*x*^{2} + *x* – 6

= 2*x*^{2} + 4*x* - 3*x* - 6

= 2*x*(*x* + 2) - 3(*x* + 2)

= (*x* + 2)(2*x* - 3)

Roots of this equation are the values for which (*x* + 2)(2*x* - 3) = 0

∴

*x*+ 2 = 0 or 2*x*- 3 = 0⇒ *x* = -2 or *x* = `3/2`

Concept: Solutions of Quadratic Equations by Factorization

Is there an error in this question or solution?

#### APPEARS IN

Advertisement Remove all ads